FAKTOR-FAKTOR YANG MEMPENGARUHI PREFERENSI KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN DI WEBSITE K24Klik.com APOTEK K24 CIKIJING TAHUN 2024 - Dede Ilma Rohmawati; Ganjar M Disastra (POLITEKNIK LP3I JAKARTA, 2024)
Online drug purchases have become a popular choice among consumers in the growing digital era, especially in Indonesia, where online pharmacy services are increasingly attracting people to meet their health needs in a more efficient and practical way. This study aims to analyze the factors that influence consumer preferences for drug purchase decisions on the K24Klik.com Apotek K24 Cikijing website. Descriptive quantitative methods were used to collect data from 100 respondents through structured questionnaires. The variables studied include the practicality of the purchasing process, security, service quality, convenience, and consumer trust in the K24 Pharmacy. The results showed that the efficient payment process, responsiveness to customer inquiries, ease of communicating with the pharmacy, and previous experience with the K24Klik.com website should be improved. Keywords: Factors, Consumer Preference, Website